Presentation patterns in women with pelvic venous disorders differ based on age of presentation. (March 2021) - Sulakvelidze, Levan; Tran, Maxwell; Kennedy, Richard; Lakhanpal, Sanjiv; Pappas, Peter J
Background: The prevalence and presentation patterns in women with pelvic venous disorders (PeVD) secondary to pelvic venous insufficiency (PVI) at various ages are ill-defined. The purpose of this investigation was to determine if the types of symptoms, interventions, and treatment outcomes of women with PeVD varied with age progression. Methods: From January 2015 to December 2019, we retrospectively reviewed prospectively collected data on 1, 280 women with PeVD from our electronic medical record at the Center for Vascular Medicine (CVM). Medical and surgical comorbidities, past medical history, presenting pelvic and lower extremity symptoms, Clinical, Etiology, Anatomy, Pathophysiology (CEAP) class, revised Venous Clinical Severity Score (rVCSS), visual analog pain score (VAS) and types of interventions were assessed. Patients were grouped into five categories based on age of initial presentation: 20–29, 30–39, 40–49, 50–59, and greater than or equal to 60. Patients were also subcategorized according to their course of treatment: Iliac venous stenting alone, ovarian vein embolization (OVE) alone, simultaneous iliac vein stenting and ovarian vein embolization, and staged iliac vein stenting and ovarian vein embolization. Differences in groups were analyzed utilizing chi square, analysis of variance and regression analysis with Graphpad Prism 8 (San Diego, CA) and SAS Studio 3.8 (Cary, NC) statistical software. Results: From January 2015 through December 2019, 1, 280 women were treated for PeVD. The average ages in each group were the following: 26.53 ± 2.90 (n = 57), 35.80 ± 2.84 (n = 238), 44.98 ± 2.78 (n = 345), 54.67 ± 2.90 (n = 324) and 68.39 ± 8.44 (n = 316) respectively. The prevalence of PVI by age group was 4.45%, 18.59%, 26.95%, 25.31% and 24.70% respectively (p < 0.05). The prevalence of diabetes, hypertension, coronary artery disease (CAD) and hypercholesterolemia differed between age groups (p < 0.05). Significant differences in the prevalence of pelvic pain, dyspareunia, dysmenorrhea, vulvar varices, leg pain, leg edema, leg heaviness, restless legs, varicose veins, and leg ulcers were observed across treatment groups (p < 0.05). CEAP distribution differed by age with CEAP 0–2 decreasing with age, CEAP 3 progressively increasing with age and CEAP 4–6 predominantly observed in patients older than 50. Analysis of variance indicated that with each decile increase in age, the prevalence of leg symptoms increased (p < 0.05) with a reciprocal decrease in pelvic symptoms (p < 0.05). All intervention types were infrequent in twenty year old's. There was a linear increase in stenting with each decile increase in age. The prevalence of OVE was similar across all age groups. There was an overall improvement in VAS scores for all treatment and age groups. For patients in their 20 s, an initial improvement in VAS scores was observed with moderate recurrence of pain observed after three months. Conclusion: PeVD presents as a spectrum of signs and symptoms, with pelvic and leg symptoms being inversely related according to age. The prevalence of PeVD is lowest in patients in their twenties with differences in presentation observed with increasing age. Venous stenting progressively increases with each decile of age whereas the prevalence of OVE is similar regardless of age. There is overall improvement in symptoms post intervention, although women in their 20 s do not respond as well to intervention as women in other age groups. Future investigations will focus on determining which pelvic venous lesion is the predominant factor that needs correction to achieve maximal pain reduction.